Structure, Identity, and Solidarity - Willer, Robb; Flynn, Francis J.; Zak, Sonya (Administrative Science Quarterly, 2012)
Here we propose an account of the link between exchange structure and the emergence of solidarity capable of accounting for the conflicting evidence social scientists have found regarding the relationship between social exchange structures and the emergence of intangible, affectively laden group sentiments. We argue that benefits received through exchange foster group identification and solidarity but that this effect is stronger in generalized exchange systems—in which giving and receiving of resources occurs unilaterally among three or more individuals—than direct exchange systems—which feature reciprocal transfers of resources between two people. At low levels of benefit to recipients, generalized and direct exchange systems will produce similarly low levels of group identification. At high levels of benefit, however, generalized exchange will result in relatively higher levels of identification. Higher levels of identification leads individual members in turn to view the group as higher in solidarity. We find support for this mediated moderation model in two survey-based case studies of organizations designed to facilitate these forms of exchange: one of Freecycle, a large-scale, online generalized exchange system, the other of Craigslist, a comparable direct exchange system. The results further suggest that generalized exchange is likely to emerge where a critical mass of exchange benefits creates positive sentiments toward the group, sentiments that help fuel further contributions in the exchange system.